Toothpick-induced superior mesenteric artery -duodenal fistula with thrombosis: a rare case report - Sun, Zhenlin; Lu, Minmin; Ding, Xiaorui; Xue, Chunxia (Frontiers in Surgery, 2025)
BackgroundIngestion of foreign bodies, particularly sharp objects like toothpicks, can lead to severe gastrointestinal complications. This case report describes a rare instance of a superior mesenteric artery (SMA)-duodenal fistula with subsequent SMA thrombosis caused by a toothpick.Case presentationA 47-year-old woman presented with persistent upper abdominal pain. Abdominal CT revealed increased density around the pancreatic neck. Further CT reconstruction identified a linear foreign body in the duodenum, which was confirmed as a toothpick during surgery. The toothpick had perforated the duodenum and pancreas. Postoperatively, the patient developed lower abdominal pain, melena, and declining hemoglobin levels. Enhanced CT indicated SMA thrombosis. Despite attempts to recanalize the SMA, conservative management was pursued due to good collateral circulation. The patient recovered well and was discharged after stabilization.ConclusionThis case highlights the potential for toothpick ingestion to cause rare and severe complications, including fistula formation and arterial thrombosis. Clinicians should be vigilant about foreign body ingestion in cases of unexplained abdominal pain and consider comprehensive management strategies to prevent catastrophic outcomes.